2005
DOI: 10.1126/science.1118611
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Liquid Aluminum at the Interface with Sapphire

Abstract: Understanding the nature of solid-liquid interfaces is important for many processes of technological interest, such as solidification, liquid-phase epitaxial growth, wetting, liquid-phase joining, crystal growth, and lubrication. Recent studies have reported on indirect evidence of density fluctuations at solid-liquid interfaces on the basis of x-ray scattering methods that have been complemented by atomistic simulations. We provide evidence for ordering of liquid atoms adjacent to an interface with a crystal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(137 citation statements)
references
References 27 publications
9
125
0
3
Order By: Relevance
“…Given the purely additive contribution of each layer to the dielectric strength in our experimental configuration 33 , we might imagine a higher BOO in proximity to the interfaces, penetrating for a few nanometres. Such a length scale is larger than has been observed in metallic liquids in proximity to the crystal growth front 34 , where only a few atomic layers are affected. We were able to fit the interfacial excess in De N with a single exponential with a characteristic decay length of 5.9 ± 1.0 nm.…”
Section: Resultsmentioning
confidence: 78%
“…Given the purely additive contribution of each layer to the dielectric strength in our experimental configuration 33 , we might imagine a higher BOO in proximity to the interfaces, penetrating for a few nanometres. Such a length scale is larger than has been observed in metallic liquids in proximity to the crystal growth front 34 , where only a few atomic layers are affected. We were able to fit the interfacial excess in De N with a single exponential with a characteristic decay length of 5.9 ± 1.0 nm.…”
Section: Resultsmentioning
confidence: 78%
“…It is reasonable to consider that the special structures are relevant to the specific heat increase. Oh et al experimentally observed ordered liquid aluminum atoms adjacent to the crystalline interface with sapphire [46]. Additionally, molecular dynamics simulations showed the formation of a dense (compressed) layer with a certain thickness at the interface between a solid nanoparticle and liquid molecules [30].…”
Section: Resultsmentioning
confidence: 99%
“…This is the case when ordering in the liquid [71,72] is necessary for crystallization [73]. The activation energy of crystallization in a number of metals and alloys is the same as for diffusion [74].…”
Section: Dendrite Growth In Undercooled Glass-forming Cu 50 Zr 50 Alloymentioning
confidence: 99%